The process of an emergency situation development at a guarded critical infrastructure facility - Azarenko , Elena; Honcharenko , Yuliia; Divizinyuk, Mykhailo; Mirnenko, Volodymyr; Syrytsia , Iuliia; Oliferuk , Volodymyr (Social Development and Security, 2019)
In the paper, it is given a description of an emergency situation development at a guarded critical infrastructure facility in the interests of the subsequent development of hazardous phenomena models specific to each enterprise. Primarily there have been formulated postulates that determine the solution of fundamental and applied tasks associated with the concept (term) of an emergency situation. Firstly, it is an objective spatio-temporal process that has its spatial and temporal scales. Secondly, this process takes place in a space defined by the corresponding spatial scales. Thirdly, this process is determined by a short-term event or a set of short-term events during which one or more parameters describing a situation or an occurring event change with the largest (maximum, extreme) gradients. Taken into account these postulates for the description of an emergency situation as a spatio-temporal process, it is necessary to use three criteria namely: a clear definition of the type of catastrophic event as a result of which the researched emergency situation is being formed, the probability of this event and a degree of reduction of its negative consequences. The process of an emergency situation development bases on the main starting point, namely a catastrophic event that can happen. So the spatio-temporal process of an emergency situation development consists of five main stages. The first is the stage of everyday accumulation of negative factors. The second is the stage of extreme accumulation of one or several negative factors. The third stage - the catastrophic event itself. The fourth stage is the stage of liquidation of the consequences of a catastrophic event. The fifth stage is the long-term consequences of a catastrophic event.